Upaya Penggunaan Media Calistung untuk Meningkatkan Keterampilan Literasi dan Numerasi Siswa Kelas 4 dan 5 Sekolah Dasar - ‘Athiqoh, Nadhiya Yasmin; Rahmawati, Lutfia Diva; Tanaya, Aurura Salsa Adila; Fatmawati, Choir Putri; Salsabila, Dewi Ula; Surya, Ulvia Ika (Merdeka Belajar Kampus Merdeka, 2024)
Elementary school students' literacy and numeracy skills are an important foundation in developing cognitive competence and future academic success. However, grade 4 and 5 students at Balongbendo Elementary School face challenges in improving these skills due to limited innovative learning media. This study aims to explore the effectiveness of using Calistung media in improving students' literacy and numeracy at the school. This study used a qualitative-descriptive method. The results showed that the use of Calistung media increased students' literacy skills by 25% and numeracy skills by 30%. This media has been proven effective in increasing students' learning motivation through an interactive and fun approach. This study provides new contributions to the development of media-based learning methods, especially in the use of Calistung media to support literacy and numeracy in elementary education. The implementation of this media not only improves student learning outcomes but also provides practical insights for teachers in designing more effective learning. It is hoped that these findings can be a reference for policy makers and education practitioners in improving the quality of learning in elementary schools. Kemampuan literasi dan numerasi siswa sekolah dasar merupakan fondasi penting dalam pengembangan kompetensi kognitif dan keberhasilan akademik di masa depan. Namun, siswa kelas 4 dan 5 di SD Negeri Balongbendo menghadapi tantangan dalam meningkatkan keterampilan ini akibat keterbatasan media pembelajaran yang inovatif. Penelitian ini bertujuan untuk mengeksplorasi efektivitas penggunaan media Calistung dalam meningkatkan literasi dan numerasi siswa di sekolah tersebut. Penelitian ini menggunakan metode kualitatif-deskriptif. Hasil penelitian menunjukkan bahwa penggunaan media Calistung meningkatkan keterampilan literasi siswa sebesar 25% dan keterampilan numerasi sebesar 30%. Media ini terbukti efektif dalam meningkatkan motivasi belajar siswa melalui pendekatan yang interaktif dan menyenangkan. Penelitian ini memberikan kontribusi baru dalam pengembangan metode pembelajaran berbasis media, khususnya pada penggunaan media Calistung untuk mendukung literasi dan numerasi di pendidikan dasar. Implementasi media ini tidak hanya meningkatkan hasil belajar siswa tetapi juga memberikan wawasan praktis bagi guru dalam mendesain pembelajaran yang lebih efektif. Diharapkan temuan ini dapat menjadi referensi bagi pengambil kebijakan dan praktisi pendidikan dalam meningkatkan kualitas pembelajaran di sekolah dasar.